ADAM8 in invasive cancers: links to tumor progression, metastasis, and chemoresistance. (11th January 2019) - Conrad, Catharina; Benzel, Julia; Dorzweiler, Kristina; Cook, Lena; Schlomann, Uwe; Zarbock, Alexander; Slater, Emily P.; Nimsky, Christopher; Bartsch, Jörg W.
Abstract : Ectodomain shedding of extracellular and membrane proteins is of fundamental importance for cell–cell communication in neoplasias. A Disintegrin And Metalloproteinase (ADAM) proteases constitute a family of multifunctional, membrane-bound proteins with traditional sheddase functions. Their protumorigenic potential has been attributed to both, essential (ADAM10 and ADAM17) and 'dispensable' ADAM proteases (ADAM8, 9, 12, 15, and 19). Of specific interest in this review is the ADAM proteinase ADAM8 that has been identified as a significant player in aggressive malignancies including breast, pancreatic, and brain cancer. High expression levels of ADAM8 are associated with invasiveness and predict a poor patient outcome, indicating a prognostic and diagnostic potential of ADAM8. Current knowledge of substrates and interaction partners gave rise to the hypothesis that ADAM8 dysregulation affects diverse processes in tumor biology, attributable to different functional cores of the multidomain enzyme. Proteolytic degradation of extracellular matrix (ECM) components, cleavage of cell surface proteins, and subsequent release of soluble ectodomains promote cancer progression via induction of angiogenesis and metastasis. Moreover, there is increasing evidence for significance of a non-proteolytic function of ADAM8. With the disintegrin (DIS) domain ADAM8 binds integrins such as β1 integrin, thereby activating integrin signaling pathways. The cytoplasmic domain is critical for that activation and involves focal adhesion kinase (FAK), extracellular regulated kinase (ERK1/2), and protein kinase B (AKT/PKB) signaling, further contributing to cancer progression and mediating chemoresistance against first-line therapies. This review highlights the remarkable effects of ADAM8 in tumor biology, concluding that pharmacological inhibition of ADAM8 represents a promising therapeutic approach not only for monotherapy, but also for combinatorial therapies.